Aplikasi Penyeleksian Supir Terbaik Online dan Non Online - M. Diarmansyah Batubara; Evta Indra (Query: Journal of Information Systems, 2019)
A driver has different personalities in serving passengers. Many passengers always complain to the online and non-online drivers because of the lack of facilities in the selection of professional drivers and drivers who do not carry out procedures determined by the transport company. This study aims to implement an interactive online application liaison between the transport company with consumers. Information technology is very important as an expansion of learning opportunities and information acquisition in Indonesia so that this research utilizes online systems as the development of information and communication technology that can be used in the satisfaction of the Indonesian people. Based on observations, the solution offered is the Best Online And Non Online Supply Selection Application. The output of this research is that the public is able to choose the best driver every time based on the assessment of the transport company using an online system that has been selected by the best driver by online and non-online transport companies.Keywords: The Best Driver, Online Application, Online, Non Online, Transportation Companies